Carboallylation of electron-deficient alkenes by palladium/copper catalysis12. Issue 81 (26th September 2018) - Semba, Kazuhiko; Ohta, Naoki; Yano, Yuko; Nakao, Yoshiaki
Abstract : The carboallylation of electron-deficient alkenes with tetraorganosilicon reagents and allylic carbonates has been developed by palladium/copper catalysis. Abstract : A method for the carboallylation of electron-deficient alkenes with tetraorganosilicon reagents and allylic carbonates based on Pd/Cu catalysis has been developed. This method affords a wide range of structurally diverse carbon skeletons from readily available starting materials, and tolerates various functional groups.